Self-forgiveness in the Context of Personal Development in Old Age - Grochala, Joanna (Paedagogia Christiana, 2016)
The article presents the issue of self-forgiveness in the context of personal development in old age. This process is seen as very important for a constructive life review and high quality of life. Initially, there is analysis of the concept of forgiveness, which derives mostly from the Judeo-Christian tradition. Then, the process is related to the human aging and different attitudes and obstacles. In the final part of the article there is a reference to the educational practice, related to supporting the development of the elderly in biographical work.